Analisis Kesadaran Hukum Pemilik Usaha Coffee Shop di Kota Serang terhadap Pendaftaran Merek - Siti Shefiani; Fuqoha (CV Rewang Rencang, 2025)
Coffee shop is one of the places that is in vogue in all circles, especially among teenagers so that this place is never empty of enthusiasts. Although many entrepreneurs have realized the importance of trademark registration, there are still some who do not fully understand this, including among coffee shop entrepreneurs. This is one of the efforts for competitors to conduct unfair business competition. It is therefore necessary to conduct socialization and education on the importance of trademark registration, simplify registration procedures and provide consultations for entrepreneurs who want to register their trademarks.